The upstream regulatory mechanism of BplMYB46 and the function of upstream regulatory factors that mediate resistance to stress in Betula platyphylla - Guo, Huiyan; Sun, Xiaomeng; Wang, Bo; Wu, Di; Sun, Hu; Wang, Yucheng (Frontiers in Plant Science, 2022)
Previously, we have shown that the transcription factor BplMYB46 in Betula platyphylla can enhance tolerance to salt and osmotic stress and promote secondary cell wall deposition, and we characterized its downstream regulatory mechanism. However, its upstream regulatory mechanism remains unclear. Here, the promoter activity and upstream regulatory factors of BplMYB46 were studied. Analyses of β-glucuronidase (GUS) staining and activity indicated that BplMYB46 promoter was specific temporal and spatial expression, and its expression can be induced by salt and osmotic stress. We identified three upstream regulatory factors of BplMYB46: BpDof1, BpWRKY3, and BpbZIP3. Yeast-one hybrid assays, GUS activity, chromatin immunoprecipitation, and quantitative real-time polymerase chain reaction revealed that BpDof1, BpWRKY3, and BpbZIP3 can directly regulate the expression of BplMYB46 by specifically binding to Dof, W-box, and ABRE elements in the BplMYB46 promoter, respectively. BpDof1, BpWRKY3, and BpbZIP3 were all localized to the nucleus, and the expression of BpDof1, BpWRKY3, and BpbZIP3 can be induced by stress. Overexpression of BpDof1, BpWRKY3, and BpbZIP3 conferred resistance to salt and osmotic stress. The results of our study provide new insights into the upstream regulatory mechanism of BplMYB46 and reveal new upstream regulatory genes that mediate resistance to adverse environments. The genes identified in our study provide novel targets for the breeding of forest tree species.